Design route towards a PM machine for rotorcraft environments. Issue 17 (4th April 2019) - North, Dominic; Yon, Jason; Baker, James; Booker, Julian; Mellor, Phil
Abstract : This paper discusses the design route followed in the development of a permanent magnet (PM) machine for electrical power generation on board a rotorcraft (helicopter). The focus of the machine design is to optimise system power density, efficiency, and robustness – all of which are crucial considerations in aerospace applications. A matrix of designs was created consisting of two stators with different winding conductors – copper and aluminium – and three rotors, each using different containment sleeve materials. These include two semi‐permeable metallic sleeves, which act to decrease the effective air gap. Combinations of the different materials will yield different system‐level power densities and efficiencies. Here, all the designs are presented along with the initial test results for the baseline machine combination validating the design predictions.